Massive and rapid COVID-19 testing is feasible by extraction-free SARS-CoV-2 RT-PCR - Smyrlaki, Ioanna; Ekman, Martin; Lentini, Antonio; Rufino de Sousa, Nuno; Papanicolaou, Natali; Vondracek, Martin; Aarum, Johan; Safari, Hamzah; Muradrasoli, Shaman; Rothfuchs, Antonio Gigliotti; Albert, Jan; Högberg, Björn; et al. (Nature communications, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is commonly diagnosed by reverse transcription polymerase chain reaction (RT-PCR) to detect viral RNA in patient samples, but RNA extraction constitutes a major bottleneck in current testing. Methodological simplification could increase diagnostic availability and efficiency, benefitting patient care and infection control. Here, we describe methods circumventing RNA extraction in COVID-19 testing by performing RT-PCR directly on heat-inactivated or lysed samples. Our data, including benchmarking using 597 clinical patient samples and a standardised diagnostic system, demonstrate that direct RT-PCR is viable option to extraction-based tests. Using controlled amounts of active SARS-CoV-2, we confirm effectiveness of heat inactivation by plaque assay and evaluate various generic buffers as transport medium for direct RT-PCR. Significant savings in time and cost are achieved through RNA-extraction-free protocols that are directly compatible with established PCR-based testing pipelines. This could aid expansion of COVID-19 testing. SARS-CoV-2 infection is widely diagnosed by RT-PCR, but RNA extraction is a bottleneck for fast and cheap diagnosis. Here, the authors develop protocols to perform RT-PCR directly on heat-inactivated subject samples or samples lysed with readily available detergents and benchmark performance against 597 clinically diagnosed patient samples.